Genetic variation and recombination analysis of the GP5 gene of the porcine reproductive and respiratory syndrome virus in Thailand - Zheng, Yajie; Li, Gan; Liu, Kexin; Luo, Qin; Sun, Wenchao; Zhao, Mengmeng (Frontiers in Veterinary Science, 2024)
Introduction Porcine reproductive and respiratory syndrome (PRRS) is a significant threat to the global swine industry, and its prevalence in Thailand spans over two decades. Methods To understand the genetic variation and recombination of the PRRS virus (PRRSV) GP5 gene in Thailand, we retrieved 726 GP5 gene sequences from the NCBI database. Phylogenetic trees were constructed using the neighbor-joining (NJ) and maximum likelihood (ML) methods, and recombination analysis was performed. Results Homology analysis was conducted on 83 PRRSV-1 and 83 PRRSV-2 strains. Phylogenetic analysis revealed the prevalence of both PRRSV-1 and PRRSV-2 strains in Thailand, with the latter exhibiting wider distribution. PRRSV-1 strains clustered into clades A, D, and H, while PRRSV-2 strains grouped into lineages 1, 5, and sublineage 8.7, further divided into 8.7/HP and 8.7/NA sublineages. Sublineage 8.7/NA strains accounted for a significant proportion of circulating PRRSV-2 strains. Homology analysis showed nucleotide and amino acid similarities ranging from 75.4 to 100.0% and 41.3 to 100.0% for PRRSV-1, and 78.6 to 100.0% and 70.8 to 100.0% for PRRSV-2 strains. Amino acid sequence alignments revealed mutations, insertions, and deletions in PRRSV-1 GP5, and key residue mutations in PRRSV-2 GP5 associated with biological functions. Recombination analysis identified two recombination events within PRRSV-2 sublineage 8.7 strains. Discussion These findings confirm the variability of the GP5 protein. This study enhances our understanding of PRRSV prevalence and genetic variation in Thailand, contributing valuable insights for PRRS prevention and control.